2007
DOI: 10.1161/atvbaha.106.129957
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Interrupts Interleukin-1β Signaling in Vascular Smooth Muscle Cells

Abstract: Objectives-Apolipoprotein E (apoE) exerts antiatherogenic effects but precise mechanisms remain unclear. We here investigated the effect of apoE on intracellular signaling by interleukin-1␤ (IL-1␤), a proinflammatory cytokine present in atherosclerotic lesions. Methods and Results-IL-1␤-induced expression and activation of inducible nitric oxide synthase and cyclooxygenase-2 were inhibited by apoE in vascular smooth muscle cells (VSMCs). These inhibitory effects were linked to the suppression of both NF-B and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…35,36 Previous studies have demonstrated that TRAF6 deficiency reduces neointimal formation and remodeling after carotid artery ligation by inhibiting inflammatory cell infiltration and matrix degrading protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Previous studies have demonstrated that TRAF6 deficiency reduces neointimal formation and remodeling after carotid artery ligation by inhibiting inflammatory cell infiltration and matrix degrading protease activity.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism is also consistent with previous reports that 1) both the apoE [130][131][132][133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] peptide and the apoE holoprotein bind to LRP (3,19); 2) apoE[133-149] can be detected inside cells (this paper), and the apoE holoprotein has also been found inside cells (37); 3) both apoE-mimetic peptides and apoE holoprotein inhibit production of NO, TNF-a, and other cytokines (15,16,18); and 4) both apoEmimetic peptides and apoE holoprotein reduce NF-kB activation through inhibition of IKK phosphorylation (20,21). These data, when coupled with the current demonstration that both the apoEmimetic peptides and the apoE holoprotein bind to SET, suggest that the peptides are true mimetics of the apoE protein in receptor binding and SET binding activities.…”
Section: Discussionmentioning
confidence: 90%
“…Clues to the molecular mechanism can be derived from the reports of Kawamura et al and Singh et al (20,21) Kawamura and coworkers (20) reported that the apoE holoprotein inhibits IL-1b signaling in vascular smooth muscle cells, resulting in reduced production of inflammatory mediators, including NO and PGE 2 . This effect was shown to be mediated through decreased phosphorylation and reduction of nuclear localized NF-kB leading to reduced production of inducible NO synthase (22).…”
mentioning
confidence: 99%
“…43 The increase in IL-18 transcription, as observed in the present study, is consistent with a recent report that apoE is a negative regulator of IL-18. 44 Overall, it is apparent that cytokines not only regulate immune or inflammatory responses in atherosclerosis but also contribute to glucose homeostasis 45 in the SMC compartment.…”
Section: Il-18mentioning
confidence: 99%